MGMT is down-regulated independently of promoter DNA methylation in rats with all-trans retinoic acid-induced spina bifida aperta - He-Nan Zhang; Yi Guo; Wei Ma; Jia Xue; Wei-Lin Wang; Zheng-Wei Yuan (Neural Regeneration Research, 2019)
O6-methylguanine DNA methyltransferase (MGMT), a DNA repair enzyme, has been reported in some congenital malformations, but it is less frequently reported in neural tube defects. This study investigated MGMT mRNA expression and methylation levels in the early embryo and in different embryonic stages, as well as the relationship between MGMT and neural tube defects. Spina bifida aperta was induced in rats by a single intragastric administration of all-trans retinoic acid on embryonic day (E) 10, whereas normal control rats received the same amount of olive oil on the same embryonic day. DNA damage was assessed by detecting γ-H2A.X in spina bifida aperta rats. Real time-polymerase chain reaction was used to examine mRNA expression of MGMT in normal control and spina bifida aperta rats. In normal controls, the MGMT mRNA expression decreased with increasing embryonic days, and was remarkably reduced from E11 to E14, reaching a minimum at E18. In the spina bifida aperta model, γ-H2A.X protein expression was increased, and mRNA expression of MGMT was markedly decreased on E14, E16, and E18. Bisulfite sequencing polymerase chain reaction for MGMT promoter methylation demonstrated that almost all CpG sites in the MGMT promoter remained unmethylated in both spina bifida aperta rats and normal controls, and there was no significant difference in methylation level between the two groups on either E14 or E18. Our results show that DNA damage occurs in spina bifida aperta rats. The mRNA expression of MGMT is downregulated, and this downregulation is independent of promoter DNA methylation.